Hypertension Education as An Effort to Increase Knowledge and Prevent Hypertension in The Elderly at Posyandu Mawar Merah, Labuh Baru Barat Sub-District, Payung Sekaki District, Pekanbaru - Zafrida, Siska; Budiman, Alfi; Akram, Faiz Jamal; Hamdani, Salsabila Putri (Abdimas Indonesian Journal, 2024)
Hypertension is a non-communicable disease that can attack the human body, whether it is a woman or a woman. The proportion of the elderly population in Indonesia in 2025 will increase to approximately 11.8% of the total population. Elderly health is one of the government's programs. The public health problem facing the elderly currently is the increasing number of cases of non-communicable diseases (NCDs), one of which is hypertension. Most of the elderly who live and are assisted in the Madania elderly social home suffer from hypertension. In this institution there is no blood pressure monitoring program and education about hypertension. This activity aims to understand the blood pressure picture of the elderly and increase the knowledge of the elderly about hypertension, so that they can carry out prevention and treatment independently. Activities were carried out in June 2023, in the form of education about hypertension to the elderly and measuring blood pressure. The method used is lecture and discussion using leaflet media. The activity was attended by 38 elderly people. Participants looked enthusiastic in participating in the entire activity agenda. There is an increase in knowledge after being given counseling material.